The relationship of alcohol concentration in epidural or acute sub-dural hematoma compared with vitreous humor and femoral blood - Boonyoung S. (2014)
The study of the relationship between the epidural hematoma or subdural hematoma alcohol concentration (SDHAC) compared with femoral blood (BAC) and vitreous humor alcohol concentration (VHAC). The specimens of 25 corpses (total 888 corpses) were carried out which revealed EDH or SDH, no treatment and the autopsy performed within 24 hours after death in 2006 at the Forensic Medicine Department, Maharaj Nakorn Chiang Mai hospital, Chiang Mai University. All specimens were frozen at -20°C until they were processed with Gas Chromatography Head space (GC-HS). The result showed that the relationship of SDHAC: BAC was better than VHAC:BAC. And SDHAC may have more reliable concentration at time of injury than BAC in the absorption phase prior to equilibrium. However, sub-dural hematoma should be one of the best specimens, as femoral blood and vitreous humor, for alcohol analysis in a corpse who died at the scene, no treatment and no sign of putrefaction.